P190 Registry Of Medical Technological Documents For Supporting Guidelines Accessibility. (15th August 2013) - Morozov, A; Stepanenko, A; Lishchyshyna, O; Gorokh, Y; Khachaturyan, V
Abstract : Background: The Ministry of Health of Ukraine has approved the methodology for development of medical and technological documents on the basis of evidence. The first documents on the basis of evidence were developed by multidisciplinary working groups in recent years. We can witness the process of guidelines adaptation and their implementation into health care practice. Context: It is necessary to ensure the availability of new documents for doctors, health care providers, and public. Transparency at all stages of medical and technical documents development is also very important. Description of Best Practice: The website of the registry of medical and technological documents has been created and posted at http://www.dec.gov.ua/mtd/index.html . The website includes: - Adapted clinical guidelines and unified clinical protocols of medical care developed by multidisciplinary working groups; - Draft documents submitted for public discussion; - Information on clinical topics under consideration; - Methodological materials for developers - members of multidisciplinary working groups; - Links to international sources of evidential information. The development of the content of the website continues. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: Creating a specialised website that integrates methodological materials, adapted clinical guidelines, unified clinical protocols, and information about the documents under consideration provides accessibility of documents, convenience for users, and improves confidence of professionals and the public in new documents.